1990
DOI: 10.1152/ajpregu.1990.259.1.r70
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of impaired excretion of a fluid load after cardiac denervation in dogs

Abstract: The influence of cardiac innervation on the renal response to volume expansion was investigated. Systemic hemodynamic, plasma hormone, and renal clearance measurements were made before, during, and after intravenous administration of 1,000 ml 0.9% saline over 10 min to six control and six cardiac-denervated, chloralose-anesthetized mongrel dogs. Volume expansion resulted in a two- to threefold rise in plasma atrial natriuretic peptide (ANP) concentrations and a 50% rise in glomerular filtration rate (GFR) in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The discovery of atrial natriuretic peptide (ANP), an extremely potent natriuretic substance released from atrial myocytes (De Bold, Borenstein, Veress & Sonnenberg, 1981) into the circulation in response to atrial stretch, has suggested a mechanism whereby the heart might exert a direct humoral influence on urine flow. However, in humans (Banner, Williams, Patel, Chalmers, Lightman & Yacoub, 1990) and other mammals (Pitchet, Gutkowska, Cantin & Lavallee, 1988;Williams, Travill, Noble, Drake-Holland t To whom correspondence should be addressed. it has been found previously that, even though ANP responses to atrial expansion are normal following cardiac denervation, natriuresis is attenuated in the absence of cardiac nerves.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of atrial natriuretic peptide (ANP), an extremely potent natriuretic substance released from atrial myocytes (De Bold, Borenstein, Veress & Sonnenberg, 1981) into the circulation in response to atrial stretch, has suggested a mechanism whereby the heart might exert a direct humoral influence on urine flow. However, in humans (Banner, Williams, Patel, Chalmers, Lightman & Yacoub, 1990) and other mammals (Pitchet, Gutkowska, Cantin & Lavallee, 1988;Williams, Travill, Noble, Drake-Holland t To whom correspondence should be addressed. it has been found previously that, even though ANP responses to atrial expansion are normal following cardiac denervation, natriuresis is attenuated in the absence of cardiac nerves.…”
Section: Introductionmentioning
confidence: 99%